Description of a new subspecies of Lethe gemina Leech, 1891 from northern Guangdong of China (Lepidoptera, Nymphalidae, Satyrinae) - Xue, Guo-Xi; Liu, Zhi-Fa; Li, Xiao-Juan; Li, Meng (Zootaxa, 2024)
Based upon morphological and molecular evidences, a new subspecies of Lethe gemina Leech, 1891, namely L. gemina bicolor subsp. nov., is described from northern Guangdong Province of China. The adults and genitalia of both sexes are illustrated. Differences in wing patterns of this new taxon and the seven known subspecies of L. gemina are discussed.